(untitled) (International Journal of Environmental Sciences, 2025)
Background:Hepatotoxicity are damage to the liver which can occur, for example, due to propylthiouracil (PTU) induced oxidative stress. It could be assumed that natural antioxidants such as curcumin and its nano-formulations like Curcumin-Chitosan nanoparticles (Cur-Cs-NPs) might be protective in this condition. Aims: To evaluate the protective role of Cur-Cs-NPs against PTU-induced hypothyroidism and hepatotoxicity in male rats by evaluating Gamma Glutamate, protein carbonyl, Tumor Necrosis Factor alpha TNFand histological parameters. Methods: Fifty-five adult male rats used, with fifteen in the preliminary trial and forty in the main experiment. The rats were divided into four groups (n=10 each). G1 control, G2 PTU 50 mg/kg B.W., G3 Cur-Cs-NPs 100 μg/kg B.W., and G4 PTU + Cur-Cs-NPs. Treatments administered orally for 28 days. Rhizomes of Curcuma longa used for the synthesis of Cur-Cs-NPs characterized by UV-Vis, FTIR, XRD, EDX, and zeta potential analysis. Blood samples were collected for the measurement of Protein Carbonyl (PC) and Gamma Glutamyltransferase (GGT) by ELISA; liver tissues were subjected to an analysis of histopathology by H&E staining. Results: Results indicated that PTU treatment in Group 2 raised protein carbonyl levels to 81.10 ± 4.43 ng/ml and gamma glutamate (GGT) to 4.56 ± 0.48 when compared to the control group (Group 1), which were 29.3 ± 3.29 ng/ml and 2.50 ± 0.19, respectively. Administration of Cur-Cs-NPs alone (G3) brought down protein carbonyls to 45.1 ± 3.31 ng/ml and GGT to 2.77 ±0 .18 . Histological observations detected in G4 showed binucleated and trinucleated hepatocytes with a slight increase in Kupffer cells that correspond to hepatic regeneration; therefore, it confirms the above results that Cur-Cs-NPs have a hepatoprotective effect against PTU-induced oxidative stress.. Conclusion:Histopathological analysis evidenced PTU as a significant inducer of hepatic damage.. the co-administration of Cur-Cs-NPs with PTU showed obvious signs of hepatic regeneration, including multinucleated hepatocytes and increased Kupffer cells. From these findings, it can be concluded that the antioxidant activity of Cur-Cs-NPs contributes largely to their hepatoprotective effect in PTU-induced oxidative stress and injury to the liver.